Understanding the Role of Health Education in Promoting Strengthening Exercises Among the Elderly: A Comprehensive Literature Review - Sona, James; Jeffery, Samuel (INTI International University, 2025)
The purpose of this systematic review was to assess how health education impacts awareness and exercise participation in improving exercise among older adults. Systematic searching was performed in PubMed (2017–2025) with pre-specified keywords, and peer-reviewed quantitative and qualitative papers including adults ≥60 years were considered; 12 studies meeting the methodological quality standards were assessed. There is evidence that health education interventions, particularly when integrated with multi-component or resistance exercise programs, enhance muscle strength, mobility, balance, fall prevention, and prevention of sarcopenia. Even though considerable evidence exists supporting these effects, strengthening exercise participation is low because of misconceptions regarding ageing, fear of injury, and lack of access to structured programs, particularly in rural and low-income areas. The review concludes that physiotherapist-facilitated health education and community-based interventions can increase awareness, exercise compliance, and functional independence of older individuals. These results underscore the importance of policymakers and public health systems incorporating accessible strength-training programs within standard care for the elderly to ensure healthy ageing.